2020
DOI: 10.1590/1980-265x-tce-2020-0262
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients Diagnosed or Suspected With Covid-19 in Cardiorespiratory Arrest: A Scoping Review

Abstract: Objective: to map the production of knowledge about the recommendations that can be applied in managing patients diagnosed or suspected with COVID-19 in cardiorespiratory arrest. Method: a scoping review, according to the Joanna Briggs Institute (2020) guidelines. Search was performed in ten data sources, and two electronic search engines were used; from 2001 to 2020. Results: of the 547 studies found, 14 met the inclusion and exclusion criteria. Most studies were published in 2020 (35.7%), and most studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Quanto à etapa sobre a utilização do DEA, estudo realizado na Nigéria, que teve como objetivo identificar a presença dos equipamentos necessários para RCP nos hospitais, evidenciou que o DEA estava presente em apenas 6,7% dos ambulatórios e centros de radiologia 17 . Outro estudo, realizado em Pernambuco, buscou descrever o conhecimento e a atuação da equipe de enfermagem de hospital de urgência perante a PCR, e constatou que 8,91% dos profissionais não consideraram o DEA como item essencial e pertencente ao suporte básico de vida 18 .…”
Section: Discussionunclassified
“…Quanto à etapa sobre a utilização do DEA, estudo realizado na Nigéria, que teve como objetivo identificar a presença dos equipamentos necessários para RCP nos hospitais, evidenciou que o DEA estava presente em apenas 6,7% dos ambulatórios e centros de radiologia 17 . Outro estudo, realizado em Pernambuco, buscou descrever o conhecimento e a atuação da equipe de enfermagem de hospital de urgência perante a PCR, e constatou que 8,91% dos profissionais não consideraram o DEA como item essencial e pertencente ao suporte básico de vida 18 .…”
Section: Discussionunclassified
“…As for the stage on AED use, a study carried out in Nigeria, which aimed at identifying the presence of the necessary equipment for CPR in hospitals, evidenced that there was an AED only in 6.7% of the outpatient services and radiology centers 17 . Another study, carried out in Pernambuco, sought to describe the knowledge and performance of the Urgency hospital Nursing team in relation to CPA, and found that 8.91% of the professionals did not consider the AED as an essential item or belonging to Basic Life Support 18 .…”
Section: /13mentioning
confidence: 99%
“…[9][10][11][12] Although there are disparities with regard to clinical variables and comorbidities associated with increased risk of hospitalization and mortality from COVID-19, growing evidence shows that patients with pre-existing diseases, and advanced age, are especially at risk of death due to viral infection. [13][14][15][16] Therefore, future analyses of this database can contribute to the analysis of characteristics of hospital admissions of patients affected by COVID-19. This database contains relevant information on the sociodemographic and clinical characteristics of patients hospitalized by COVID-19.…”
Section: Introductionmentioning
confidence: 99%